Голодомор 1932-1933 pp.: механізми сталінського терору - Кульчицький, С.В. (Український історичний журнал, 2007)
У статті «Голод 1932 р. в затінку голодомору-33» (УІЖ. - 2006. - №6. - С.77-97) автор показав, що голод, який панував в Україні у першій половині 1932 р., був викликаний хлібозаготівлями з урожаю 1931 р. У цій статті досліджується переростання голоду, що розпочався з жовтня 1932 р. у хлібовиробляючих регіонах СРСР (у тому числі в УСРР) внаслідок заготівель із нового врожаю, у жахливий голодомор, спричинений каральним вилученням у селян України не тільки хліба, а й усіх без винятку продовольчих запасів. Конфіскація нехлібного продовольства під прикриттям хлібозаготівельної кампанії була здійснена у два прийоми: у листопаді-грудні 1932 р. - у сотнях сіл, поставлених на «чорну дошку», а в січні 1933 р. - на всій території України. Наслідком терору голодом стала загибель упродовж листопада 1932 - червня 1933 рр. мільйонів українських громадян. Цей різновид сталінських репресій підпадає під дію Конвенції ООН «Про запобігання злочину геноциду і покарання за нього». To justify the fairness of legal determined qualification of Famine as genocide of Ukrainian people it is necessary to prove its fundamental difference from starvation of 1932 in the Ukrainian Socialistic Soviet Republic and starvation of 1932-1933 in other regions of the Soviet Union. The article «Starvation of 1932 in Shade of Famine-33» (UHJ. - 2006. - №6. - P.77-97) shows that starvation that took place in Ukraine in the first half of 1932 was caused by grain procurements from crops of 1931. This article examines overgrowing of starvation, which began in October 1932 in grain producing regions of the Union of Soviet Socialist Republics (including Ukrainian Socialistic Soviet Republic) as a result of storing up from new harvest, into an awful Famine caused by confiscation from Ukrainian peasants of all their provisions. Confiscation of non-grain provision under cover of grain procurement campaign was realized in two draughts: in November and December 1932 - in hundreds of villages put on «black board» and in January 1933 - on the whole territory of Ukraine. The result of starvation terror was death of millions of Ukrainian citizens during November 1932 - June 1933. This kind of Stalins repression is under the influence of UN Convention «About Suppression of Genocide and Punishment for It».